Unconventional monetary policy in an open economy - Jana Gieck (Deutsche Bundesbank, 2014)
The impact of unconventional monetary policies on exchange rates and its spillovers to other economies is not yet fully understood. In this paper I develop a two-country DSGE model with interbank markets and endogenous default probabilities to analyze the cross-border impacts of unconventional monetary policy. I examine the impact of two unconventional measures commonly used: central bank liquidity injections and asset swaps. I find that liquidity injections lead to a short run appreciation of domestic currency, but a mild long run depreciation. In contrast, asset swaps cause a short run depreciation of domestic currency, but a long run appreciation. Lastly, when both countries coordinate on the implementation of unconventional policies, the model yields the following results: Non-coordinated liquidity injections lead to higher increases with respect to output and inflation variation, but have negative spillovers on the other economy in terms of lower growth. By contrast, coordinating asset swaps leads to higher increases in output and lower fluctuation in inflation in both countries. The results of this paper suggest that coordination in unconventional monetary policy may not always yield an optimal outcome, and macroeconomic outcomes in both countries depend crucially on the choice of instrument.
Keywords: E02; E44; E52; G21; G28; 330; Unconventional Monetary Policy; Quantitative Easing; Asset Swaps; Open Economy DSGE; Currency Wars; Policy Coordination